Memahami Pencatatan Perkawinan di Indonesia dalam Paradigma Hukum Islam Kontemporer - Muhammad Aziz; Athoillah Islamy (Fakultas Syariah dan Ekonomi Islam, 2022)
The phenomenon of unregistered marriages is still rampant in Indonesia. Regardless of the various reasons that trigger it, empirical facts show that unregistered marriages cause many legal problems, both for the life of the family concerned, society and the state.This quality research in the form of a literature review intends to re-understand the existence of marriage registration in the Islamic legal paradigm through the contemporary sharia maqasid approach conceptualized by Jasser Auda. This research uses a normative-philosophical approach. Primary data of Law No. 1 of 1974 on Marriage and compilation of Islamic Law. Data collection techniques through documentation techniques. Meanwhile, data analysis through reduction, presentation, and verification. The results showed that the construction of the paradigm of marriage registration rules in Indonesia is in line with the contemporary Islamic legal paradigm that emphasizes holistic legal arguments, namely involving various perspectives, both normative, social, buddhist, developmental and state regulations for the realization of the benefit of marital life. The results showed that the construction of the paradigm of marriage registration rules in Indonesia is in line with the contemporary Islamic legal paradigm that emphasizes holistic legal arguments, namely involving various perspectives, both normative, social, buddhist, developmental and state regulations for the realization of the benefit of marital life. This can be proven through the various paradigms of system philosophy features elaborated by Jasser Auda as a contemporary sharia maqasid approach. The theoretical implication of this research is that a holistic Islamic legal paradigm is needed, namely through multi-perspectives, not a monolithic paradigm in understanding the implications of the benefits of marriage registration rules. The limitations of this study have not examined the Islamic legal arguments of Islamic religious leaders in Indonesia who tend to be apathetic or permissive to the phenomenon of marriage without being registered in society.